Regulating competition in the Malaysian telecommunication sector: a need for a new approach? - Abdul Rahman, Nasarudin; Ahamat, Haniff; Abdul Jalil, Juriah (Inderscience Publishers, 2014)
Abstract: The objective of a competition law is to protect the process of competition between firms in the market by preventing any anti-competitive behaviour such as cartel, abuse of dominant position and mergers that have the effect of lessening competition. However, it is often argued that network industries such as telecommunication should be excluded from the application of the generic competition law, as it has particular characteristic such as natural monopoly, the existence of high entry barriers and absence of effective competition in the market which requires continuous monitoring of the market in the form of access regulation and price control. This paper aims to analyse the existing regulatory and institutional framework overseeing competition in the Malaysian telecommunications sector. The main focus of this paper is to analyse the manner in which competition is pursued through specific sector regulation and whether specific rules on competition are effectively and rigorously enforced. This paper then explains the benefits that will arise from the application of the generic competition law to the telecommunication sector and from increasing the role of the competition authority to regulate the same.